Efficacy of Appropriate Antimicrobial Therapy on the Survival of Patients With Carbapenem Nonsusceptible Klebsiella Pneumoniae Infection. Issue 33 (August 2015) - Lin, Yi-Tsung; Chuang, Chien; Su, Chin-Fang; Chan, Yu-Jiun; Wang, Lih-Shinn; Huang, Ching-Tai; Chuang, Yin-Ching; Siu, L. Kristopher; Fung, Chang-Phone; Mahmood S, Choudhery.
<x xml:space="preserve">Abstract</x> Abstract The impact of antimicrobial treatment on the outcome of carbapenem nonsusceptible Klebsiella pneumoniae (CnsKP) infections needs to be elucidated. This nationwide, multicenter study was conducted to evaluate the impact of appropriate antimicrobial therapy on 14-day mortality among patients with CnsKP infection in Taiwan. Patients with CnsKP infections from 11 medical centers and 4 regional hospitals in Taiwan were enrolled in 2013. Carbapenem nonsusceptibility was defined as a minimum inhibitory concentration of ≥2 mg/L for imipenem or meropenem. Predictors of 14-day mortality were determined using the Cox proportional regression model. The influence of infection severity on the impact of appropriate use of antimicrobials on 14-day mortality was determined using the Acute Physiology and Chronic Health Evaluation (APACHE) II score. Overall 14-day mortality was 31.8% (49/154). Unadjusted mortality for appropriate antimicrobial therapy was 23.1% (18/78 patients). Appropriate therapy was independently associated with reduced mortality (hazard ratio [HR], 0.44; 95% confidence interval [CI], 0.24–0.80; P = 0.007). A subgroup analysis revealed that the benefit of appropriate therapy was limited to patients with higher APACHE II scores (HR for patients with scores >15 and ⩽35, 0.46; 95% CI 0.23–0.92; and for those with scores >35, 0.14; 95% CI, 0.02–0.99). In conclusion, appropriate antimicrobial therapy significantly reduces 14-day mortality for CnsKP infections. Survival benefit is more notable among more severely ill patients.